Performance of V-Cone flowmeter applied to cryogenic fluid measurement considering cavitation. Issue 6 (March 2019) - He, Denghui; Bai, Bofeng; Chen, Senlin; Zhang, Jie; Guo, Pengcheng
Abstract: The V-Cone flowmeter is a promising differential pressure flowmeter for metering the cryogenic fluid for its many advantages. When the cryogen velocity increases to a certain value, the cavitation may occur in flowmeter, which may significantly affect the performance of V-Cone flowmeter. However, the effect of cavitation on performance of V-Cone flowmeter remains unclear and there are no published studies to our knowledge on this issue. Here we investigate the performance of V-Cone flowmeter when measuring the cryogenic fluids, especially the effects of cavitation on the discharge coefficient and pressure loss coefficient of the flowmeter. Two cryogenic fluids are investigated, including liquid nitrogen (LN2 ) and liquid hydrogen (LH2 ). For comparison, the water is also investigated. The realizable κ - ε model is used to describe the turbulence. The Schnerr-Sauer cavitation model is used to investigate the effect of cavitation on the performance of the V-Cone flowmeter. The results show that there was little effect of cavitation on the discharge coefficient and pressure loss coefficient at the initial stage of cavitation. When the cloud cavitation occurred downstream of V-Cone, the discharge coefficient decreases rapidly with Reynolds number increasing, while the pressure loss coefficient rises quickly. The average discharge coefficient is almost the same for different fluids in the stable region; while the cryogenic fluids have wider stable Reynolds number ranges than the water. The lower limits of the Reynolds number for the constant discharge coefficient is very close for three fluids, however, for the upper limits of Reynolds number are quite different. We conclude that measurement range of the cryogenic fluid is much larger than that of the water, which shows that the V-Cone flowmeter exhibits great potential in the measurement of cryogenic fluid. This study provides insights into the effect of cavitation on the measurement of V-Cone flowmeter and opens a new avenue for properly choosing and using a V-Cone flowmeter for metering the cryogenic fluid.